Perancangan User Experience Aplikasi Interaksi Masyarakat Terpadu Menggunakan Metode Human-Centred Design - Arif Eka Brilian; Herman Tolle; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Malang City is one of the cities with a large population in Indonesia. In 2020, the total population of Malang City will reach 874,890. With the growth rate of population, there are problems of community interaction with the government of Malang City. One of the problems of community interaction with the government is the delivery of aspirations or complaints to the Malang City Government. Apart from these social problems, there are problems with natural disasters in Malang. In 2019, the Central Statistics Agency of Malang City recorded 201 natural disasters that occurred. Until now, Malang City has not had disaster service or disaster reporting. So far, it is known through official social media belonging to related agencies, such as BPNPB or BMKG. Apart from handling complaints and disasters, Malang City does not yet have a service to facilitate aid assistance. Responding to some of these problems, the Malang City Communication and Information Agency plans to create a mobile-based Integrated Community Interaction service application that can be used and received well by the community. Therefore, it is necessary to design the user or user experience to see whether the design as a matter of community interaction has met the needs of the community as users. The design process in this study applies the Human-Centered Design method which focuses on the needs of users and stakeholders for solution design considerations. After the design was successfully drafted, 7 evaluators evaluated the design using the Usability Testing Scenario Task method and the SUS questionnaire. Based on the evaluation results, the solution design got a value of 95.03% in the aspect of Effectiveness, and a value of 83% in the aspect of Efficiency. Meanwhile, in the Satisfaction aspect, the score was 86.07 with the following predicates; Acceptable in the Acceptable category, Promoter predicate in the Net Promotor Score category, and Excellent predicate in the Adjective category.